Bioinspired synthesis of optically and thermally responsive nanoporous membranes - Morones Ramírez, José Rubén (2013)
The development of porous membranes that can rapidly change flow rates in response to external, noninvasive stimuli has broad technological applications for areas ranging from biomedical devices to architecture. Environmentally responsive membranes have a fundamental role in the development of devices used in chemical sensors, biological sorters, sequencing, separations, high-throughput medical devices and labs on a chip. The design and engineering of these responsive porous membranes have been achieved through the coupling of porous membranes with polymeric materials that can change their physical conformation in response to pressure, heat, pH or different chemical entities. Inspired by the phototropic growth of coleoptiles and the light-mediated mechanism that plants use to open their stomata, in this work, light-responsive porous membranes were engineered, mathematically modeled and synthesized. This biologically inspired approach led to a state-of-the-art design technique and a device that outperforms its natural counterpart and is capable of reversibly controlling flow rates from 0.001 to 0.035 ml s 1 cm2 in less than a few minutes using the noninvasive stimulus of light. We envision that the polymeric responsive membranes and the platform synthesis technique employed in this manuscript for their fabrication could be utilized in a broad range of applications and will have a great impact on the fields of fluid handling, biomedical high-throughput devices, sensors, medicine and other fields of chemistry, biology and mechanical engineering. NPG Asia Materials (2013) 5, e52; doi:10.1038/am.2013.23; published online 21 June 2013